Pembelajaran IPS Berbasis Cerita Rakyat Asal Usul Desa Sokaraja untuk Menanamkan Karakter pada Siswa - Anjarwati, Titis; Maryono; Muhtar Sofwan Hidayat (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This research was conducted at SD N 2 Sokaraja using qualitative methods. Qualitative methods are research that does not use mathematical, statistical or computer models. The aim of this thesis research is to: 1) To find out how social studies learning based on the folklore "Origins of Sokaraja Village" is implemented at SD N 2 Sokaraja; 2) To find out what characters can be instilled in grade 3 students at SD N 2 Sokaraja; 3) To determine the inhibiting and supporting factors in implementing folklore-based learning at SD N 2 Sokaraja. With data collection techniques using observation, interviews and documentation. The results of this research are that the application of folklore-based learning is effective for grade 3 students at SD N 2 Sokaraja. Learning is more interactive and varied, resulting in enthusiastic students. Using the 2022 edition of the Social Sciences book, this learning is carried out in the Social Sciences or social learning chapter. Where certain chapters are the main chapters for assessing student attitudes or student character. It was found that several characters appeared in the story that could be instilled in students. As a result, students can learn and take moral messages about characters that appear and are relevant in everyday life. However, several obstacles were found, such as inadequate facilities, the nature of oral stories where the original version is easily lost, and limited knowledge of educators. But there are also supporting factors, such as this learning is supported by the local community and this learning can make it easier for teachers to assess students' attitudes through role-playing activities.